2017
DOI: 10.1159/000479903
|View full text |Cite
|
Sign up to set email alerts
|

MiR-143-5p Deficiency Triggers EMT and Metastasis by Targeting HIF-1α in Gallbladder Cancer

Abstract: Background/Aims: Early metastasis plays a pivotal role in tumor-caused death in gallbladder cancer (GBC) patients. Increasing evidence suggest that miR-143-5p is an active player involved in cancer metastasis and a potential therapeutic target. However, its role in the development of GBC cells remains unclear. The aim of this study is to reveal the inhibiting effects of miR-143-5p on the proliferation and metastasis in GBC. Methods: Quantitative real-time PCR were used to investigate miR-143-5p and its target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…Activated Twist induces the up-regulation in N-cadherin and down-regulation in E-cadherin (46). Furthermore, miR-143-5p has been shown to exert an inhibitory effect on gallbladder cancer proliferation and metastasis by reducing the expression of HIF-1a, which further down-regulated Twist1 and impeded EMT process (47). Snail1 is a transcriptional repressor of E-cadherin that triggers EMT (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated Twist induces the up-regulation in N-cadherin and down-regulation in E-cadherin (46). Furthermore, miR-143-5p has been shown to exert an inhibitory effect on gallbladder cancer proliferation and metastasis by reducing the expression of HIF-1a, which further down-regulated Twist1 and impeded EMT process (47). Snail1 is a transcriptional repressor of E-cadherin that triggers EMT (48).…”
Section: Discussionmentioning
confidence: 99%
“…In order to further verify the binding activity of miR-143-5p to LAMP3 and HAGLR, RNA pull-down assay was performed. NC-bio-probe that could not be bound by LAMP3 and HAGLR was employed as the NC, with hypoxia-inducible factor (HIF)-1a, which has been previously confirmed to bind to miR-143-5p (29), serving as the positive control. In contrast to Mut-miR-143-5p, the enrichment of HAGLR and LAMP3 was remarkably elevated in WT-miR-143-5p (P , 0.05), indicating direct binding between miR-143-5p and HAGLR as well as a direct binding between LAMP3 and miR-143-5p (Fig.…”
Section: Ec Tissues Exhibit Enhanced Epithelial-mesenchymal Transitionmentioning
confidence: 99%
“…Moreover, miR-143-5p deficiency in gallbladder cancer triggered the EMT and metastasis by targeting HIF-1α in mesothelioma. 27 miR-143-3p suppresses the progression of ovarian cancer and esophageal squamous cell carcinoma, 28 , 29 and miR-145-3p acts as a tumor suppressor in HNSCC by targeting MYO1B . 30 Despite some evidence that miRNAs in the 143/145 group may be co-regulated, 31 in the context of the current work, we did not evaluate the expression of miRNAs other than miR-145-5p, given our focus on FSCN1 .…”
Section: Discussionmentioning
confidence: 99%
“…12 Epithelial-interstitial transformation (EMT) is a process in which epithelial cells lose their original polarity, thus obtaining anti-apoptosis, high migration, and invasion ability, and transforming into interstitial cells. 22 However, the occurrence of DDR1 and EMT is also closely related. Reports 23 once showed that the upregulation of DDR1 can promote the development of colorectal cancer by reducing the expression of E-Cadherin.…”
Section: Discussionmentioning
confidence: 99%